RNA helicase Belle (DDX3) is essential for male germline stem cell maintenance and division in Drosophila. - Kotov, A.A.; Olenkina, O.M.; Kibanov, M.V.; Olenina, L.V. (Biochimica et Biophysica Acta, 2016)
The present study showed that RNA helicase Belle (DDX3) was required intrinsically for mitotic progression and survival of germline stem cells (GSCs) and spermatogonial cells in the Drosophila melanogaster testes. We found that deficiency of Belle in the male germline resulted in a strong germ cell loss phenotype. Early germ cells are lost through cell death, whereas somatic hub and cyst cell populations are maintained. The observed phenotype is related to that of the human Sertoli Cell-Only Syndrome caused by the loss of DBY (DDX3) expression in the human testes and results in a complete lack of germ cells with preservation of somatic Sertoli cells. We found the hallmarks of mitotic G2 delay in early germ cells of the larval testes of bel mutants. Both mitotic cyclins, A and B, are markedly reduced in the gonads of bel mutants. Transcription levels of cycB and cycA decrease significantly in the testes of hypomorph bel mutants. Overexpression of Cyclin B in the germline partially rescues germ cell survival, mitotic progression and fertility in the bel-RNAi knockdown testes. Taken together, these results suggest that a role of Belle in GSC maintenance and regulation of early germ cell divisions is associated with the expression control of mitotic cyclins.